السياق في تحديد المعنى - Masnal Jazuli (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2016)
AbstractDictionary is not enough to give a meaning of a particular word or sentence. Therefore, one needs meaning in context to formulate the meaning in order to make sure the intended meaning, particularly the meaning of Holy Quran. It is no doubt that the similar meaning (synonym) has an effect on expansion. It gives a particular meaning on a certain sentence. As a result, meaning is sometimes restricted and can not be intercpreted freely. It is safe to say that semantically, the meaning is restricted on a certain meaning. Pragmatically, howevers, meaning needs a context. So that meaning and context is related each other. Context, then is needed in interpreting the use of a sentence and expression.Keyword: المعجم, الدلالة, والسياق, والتكنولوجيا